Technique for Evaluating the Uncertainty of Enthalpy of Water and Steam for Thermal Energy Metering Systems - Матіко, Федір; Слабик, Оксана; Лесовой, Леонід; Матіко, Галина; Matiko, Fedir; Slabyk, Oksana; Lesovoy, Leonid; Matiko, Halyna (Lviv Politechnic Publishing House, 2018)
У статті представлено аналіз існуючих методик розрахунку ентальпії води (водяної пари), за результатами якого визначено методики, які доцільно застосовувати для автоматизованого проектування систем обліку теплової енергії. Розроблено рівняння для розрахунку відносної розширеної невизначеності ентальпії води (водяної пари) із врахуванням методичної невизначеності обчислення ентальпії та невизначеностей результатів вимірювання температури та тиску води (водяної пари). Розроблено спрощені аналітичні залежності для обчислення відносних коефіцієнтів чутливості невизначеності ентальпії до невизначеності результатів вимірювання тиску та температури води. Ці залежності дають можливість обчислити значення коефіцієнтів чутливості для діапазону тиску від 0 до 5 МПа та температури від 300 до 550 K. Відносні відхилення значень коефіцієнтів чутливості, отриманих за спрощеними залежностями, від значень, отриманих за рівняннями Міжнародної організації властивостей води та водяної пари (IAPWS), у вказаних діапазонах тиску та температури становлять відповідно 0,48 % (для коефіцієнта чутливості невизначеності ентальпії до невизначеності тиску) і 0,56 % (для коефіцієнта чутливості невизначеності ентальпії до невизначеності температури). Розроблена спрощена методика оцінювання невизначеності ентальпії води (водяної пари) може бути застосована під час оцінювання метрологічних характеристик систем вимірювання кількості теплової енергії, а також для їх автоматизованого проектування.

The paper presents an analysis of existing techniques for calculating the enthalpy of water (steam). Based on the analysis the techniques were defined that should be applied for computer-aided design of thermal energy metering systems. Equations for calculating relative expanded uncertainty of water (steam) enthalpy are developed taking into account methodical uncertainty of enthalpy calculation and uncertainties of metering temperature and pressure of water (steam). Simplified dependencies are developed for calculating the relative sensitivity coefficients of the enthalpy uncertainty to the uncertainties of water pressure and temperature. These dependencies make it possible to calculate the values of the sensitivity coefficients for a range of pressure from 0 to 5 MPa and temperature from 300 to 550 K. The relative deviations of the sensitivity coefficients obtained by the simplified dependencies from the values obtained by the equations of International Association for the Properties of Water and Steam (IAPWS) are 0.48 % (for the sensitivity coefficient of uncertainty of enthalpy to uncertainty of pressure) and 0.56 % (for the sensitivity coefficient of uncertainty of enthalpy to uncertainty of temperature) for the above pressure and temperature ranges. The developed simplified technique for evaluating uncertainty of water (steam) enthalpy can be applied to determine the metrological characteristic of thermal energy metering systems and also for their computer-aided design.
Методика оцінювання невизначеності ентальпії води та водяної пари для систем вимірювання кількості теплової енергії
Keywords: ентальпія води; невизначеність ентальпії; методика оцінювання невизначеності; коефіцієнт чутливості; кількість теплової енергії; water enthalpy; uncertainty of enthalpy; technique for evaluating uncertainty; sensitivity coefficient; thermal energy amount